Anteroinferior plating is an independent factor for decreasing symptomatic implant removal rates after plate fixation for midshaft clavicle fractures. Issue 1 (8th March 2023) - Ariga, Akane; Shimura, Haruhiko; Fujita, Koji; Nimura, Akimoto
Abstract: Objectives: The factors that significantly influence the symptomatic implant removal rates after plate fixation for midshaft clavicle fractures remain controversial. The purpose of this study was to compare the symptomatic implant removal rates between 2 different types of plating technique and to evaluate independently associated factors. Design: Retrospective cohort study. Setting: Acute care center. Patients/Participants: A total of 71 patients 16 years or older who were diagnosed with displaced midshaft clavicle fractures from April 2016 to March 2020. Intervention: Thirty-nine patients were treated with superior plating (Group SP), and the remaining 32 patients were treated with anteroinferior plating (Group AIP). Main Outcome Measurements: Symptomatic implant removal rates after plate fixation for midshaft clavicle fractures. Results: Symptomatic implant removal rates were significantly lower in Group AIP (28.1%) than in Group SP (53.8%) ( P = 0.033). Multivariate analyses showed that symptomatic implant removal rates were significantly decreased by three independent factors, namely AIP (odds ratio [OR] = 0.323) ( P = 0.037), greater age (45 years or older) (OR = 0.312) ( P = 0.029), and high body mass index (≥25 kg/m 2 ) (OR = 0.117) ( P = 0.034). Conclusions: AIP significantly and independently decreased the symptomatic implant removal rate. Among the three explanatory factors showing significant difference, plating technique is the only factor that can be altered by medical institutions. Therefore, we recommend this technique for displaced midshaft clavicle fractures to reduce a second surgery such as symptomatic implant removal. Level of Evidence: Level 3, retrospective cohort study